Pengaruh Judi Online dan Gaya Hidup Hedonis Terhadap Perilaku Keuangan Generasi Z di Aceh Barat - Rikki Hermawan; Fitria Mandaraira (Indo Publishing, 2026)
This study aims to analyze the effect of online gambling and a hedonistic lifestyle on the financial behavior of Generation Z in West Aceh Regency. The development of digital technology has increased access to online gambling activities and encouraged hedonistic lifestyle tendencies among young people, which may affect personal financial management. This research employed a quantitative approach using a correlational method. Primary data were collected through questionnaires distributed to 100 Generation Z respondents aged 18–28 years residing in West Aceh, using purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27. The results indicate that online gambling has a negative and significant effect on the financial behavior of Generation Z. A hedonistic lifestyle also has a negative and significant effect on financial behavior. Simultaneously, online gambling and a hedonistic lifestyle significantly influence the financial behavior of Generation Z in West Aceh. This study emphasizes the importance of financial literacy and self-control in promoting healthy financial behavior in the digital era.